Parent Stress in Childhood Cancer - Basher, MAK; Karim, MR; Sultana, N; Hossain, KJ; Kamal, MM (Bangladesh Medical Journal, 2014)
The objective of the study was to assess level of stress of the parents with a child suffering from cancer. A total of 396 parents of which 146 fathers and 250 mothers were recruited from the National Institute of Cancer Research & Hospital, Bangabandhu Sheik Mujib Medical University, Dhaka Medical College Hospital and Dhaka Shishu Hospital (DSH), Dhaka from January 2011 to November 2011. They were selected consecutively on the basis of the defined criteria. The research instruments were interviewer questionnaire and stress measuring standard scales. Results showed that all of the parents were found educated. In graduate and above, fathers were comparatively higher educated than that of mothers. In profession, 48.7%(n=193) were household workers, 33.7%(n=133) service holders and 17.6%(n=70) were businessmen. The monthly family income of the respondent were Tk. 10,000 to 20,000 in 77.0%(n=305). Results also showed that 86.8%(n=344) of them in both sexes had age in between 18 to 40 years of which 44.9%(n=178) had age 31-40 years and 41.9%(n=166) were 18-30 years respectively. Only 13.2%(n=52) of both sexes had age above 40 years. The mean age of them were 33 ± 8 years. The type of cancers among the children of the respondents was described in the Table 2. The results showed that 61.4%(n=243) of the children had been suffering form leukemia, 17.4%(n=69) lymphoma, 8.3%(n=33) reticuloblastoma, 2.5%(n=10) neuroblastoma, 1.1%(n=4) solid tumors and 9.3%(n=48) were from other cancers such as embryoma, rhabdomyosarcoma, testicular tumors etc. The age of the children who had been suffering from different type of cancers was summarized in the Table-3. About 44.4%(n=176) of the children had age 1-5 years, 35.6%(n=141) age 6-10 years and 20.0%(n=79) were of age 11-15 years respectively. Leukemia was found the highest incidence among all age groups of the boys and girls. Results also showed that 63.8%(n=253) of the parents had certainly affected due to the stress. About 6.7%(n=26) of the parents had severely affected and 28.7%(n=114) may be affected induced by the cancers of their children. The poorly educated, up to class-X, fathers and mothers constituted 49.8%(n=197) were found certainly affected with the stress. Middle age group (31-40 years) having middle class socioeconomic status had also similar characteristics of the stress among the respondents. In duration of the disease at the time of assessment, results showed that 21.8%(n=86) of the parents with one child suffering from cancer in between 7-12 months were found certainly and severely affected with the stress. Careful designed investigations of the long-term psychological and behavioral consequences of the parents are vital important for early interventions to assess and treat psychological distress of them. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18773 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 8-13